The relationship between 500 m and 2000 m simulated rowing times for schoolboy rowers over a training period of three years - Petrykowski, A.; Lutoslawska, G. (Human Movement, 2011)
Available data finds that for schoolboy rowers the 2000 m on-water or laboratory rowing distance causes fatigue and depresses their ability to train during the following days. Thus, looking for a less demanding test we evaluated the relationships between 500 m and 2000 m laboratory performance in schoolboy rowers. Basic procedures. A total of 10 boys participated in the study. All of the subjects simulated rowing "all-out" in either the 500 m or 2000 m rowing distance using a Concept II ergometer (Morsville, VT, USA). The tests were performed in November (transition phase), in January (general preparation phase), in March (specific preparation phase) and in June (competitive phase) throughout three successive years of training. Main findings. The mean power output during the 2000 m row gradually increased in the second year of training vs. the first one, and in the third year of training vs. the second one (p < 0.001). The times markedly improved in each year of training (p < 0.001). The mean power output and the time of the 500 m distance improved significantly in each year of training. In each training phase during the three years of training there were significant correlations between the rowing times in the 500 m and 2000 m distances. The coefficients of determination (r2 x 100) in the first year varied from 66.9 to 85.6%, in the second year - from 62.0% to 92.3%, and in the third year - from 76.4 to 89.5%. Conclusions. The relationship between the times measured in the of the 500 m and that of 2000 m one is affected by both the annual training phase and training experience. Thus, the 500 m laboratory rowing test may be useful in assessing the ability of schoolboy rowers to perform a competitive distance, but the results require careful interpretation.